INFLUENCE OF ELECTROHYDRAULIC INJECTOR PARAMETERS ON FUEL SUPPLY PROCESS - А. Vrublevsky (Avtomobilʹnyj Transport (Harʹkov), 2010)
The results of calculation research of electrohydraulic injector for accumulator fuel equipment of high-speed diesel engine of DT type are presented in the article. As a result of obtained data analysis of fuel supply process there have been determined the limits of fuel injector constructive and adjusting changes and proportion that served as a starting point of multicriterion synthesis of electronic control injection fuel system.